Global Development Divergence and Contemporary Gravitional Process in GeoEconomic Space - Kravchuk, N. (Економічний вісник Донбасу, 2013)
From the compositional point of view, research on this topic has revealed two main directions: (1) an analysis of global development asymmetry that has activated gravitational processes in geo-economic space; and (2) a direction that focuses on the profound study of the causes for heterogeneity in geo-economic space and divergence in global development under the influence of gravitational factors of nature on the endogenousexogenous axis. Systemic determinants of gravitational processes in the geo-economic space have been revealed, a geo-strategic matrix of divergence in global development has been built, and Ukrainian geo-strategic positions in the geo-economic space in the projection of problems on global intersystem transformations have been outlined. It has been proved that the level of gravitational charge grows under conditions involving the deepening of global development asymmetries has been proved. Композиційно дослідження розгортається у двох основних напрямах: перший - аналіз асиметрій глобального розвитку, що активізують гравітаційні процеси у геоекономічному просторі; другий - зорієнтований на поглиблене вивчення причин гетерогенізації геоекономічного простору і дивергенції глобального розвитку під впливом гравітаційних факторів ендогенного та екзогенного характеру. Розкрито системні детермінанти гравітаційних процесів у геоекономічному просторі, побудовано геостратегічну матрицю дивергенції глобального розвитку, окреслено геостратегічні позиції України у геоекономічному просторі у проекції на проблематику глобальних міжсистемних трансформацій. Доведено, що рівень гравітаційного навантаження зростає в умовах поглиблення асиметрій глобального розвитку. Композиционно исследование разворачивается в двух основных направлениях: первое - анализ асимметрий глобального развития, активизирующих гравитационные процессы в геоэкономическом пространстве; второе - посвященное углубленному изучению причин гетерогенизации геоэкономического пространства и дивергенции глобального развития под влиянием гравитационных факторов эндогенного и экзогенного характера. Раскрыты системные детерминанты гравитационных процессов в геоэкономическом пространстве, построено геостратегическую матрицу дивергенции глобального развития, очерчены геостратегические позиции Украины в геоэкономическом пространстве в проекции на проблематику глобальных межсистемных трансформаций. Доказано, что уровень гравитационной нагрузки возрастает в условиях углубления асимметрий глобального развития.